Social technologies as a development strategy for the Serra da Capivara Territory (Research, Society and Development, 2023)
Social technologies can be presented in the form of products, processes or techniques resulting from the application of popular and/or scientific knowledge. This research aims to identify available social technologies, highlighting the importance of their adoption as a strategic tool for territorial development, as in the Serra da Capivara Territory. For this, a search was carried out in Banco do Brasil's Bank of Social Technologies, which covers the themes of food, education, energy, housing, environment, water resources, income and health. Information was collected regarding the awarded and certified social technologies in the 2019 and 2021 editions of the Banco do Brasil Foundation Social Technology Award. 261 social technologies were identified, 174 referring to the 2019 award, and 87 referring to the 2021 award. It was possible to observe that in both editions the themes, 'education', 'environment' and 'income' presented the highest volumes of certified social technologies. In addition, it was observed that in the two editions, 2019 and 2021, the themes 'water resources', 'energy' and 'housing' presented low quantities of certified technologies, and no awarded technology. The application of these social technologies in the Serra da Capivara Territory would imply significant improvements in the social, economic, environmental and cultural dimensions, contributing to local development. However, this requires the planning and execution of a territorial development policy focused on disseminating knowledge, identifying local problems and potential, and including communities as protagonists in this process.